2011
DOI: 10.4236/ajps.2011.21009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Integrated Nutrients on Growth, Yield and Quality of Maize (Zea mays L.)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 6 publications
3
26
0
Order By: Relevance
“…According to Uprety et al (2009), application of acidified manure can considerably increase the soil micronutrient contents; and in our case manure was provided as a base material which enhanced the micronutrients bioavailability and improved the growth and yield of maize (Bakry et al, 2009;Kruczek, 2005;Lisuma et al, 2006;Singh et al, 2009). Our findings were also in line with Tariq et al (2014); Ghaffari et al (2011);Lana et al (2007) and Baloch et al (2008) who revealed that micronutrients played a critical role in achieving higher yield and growth in maize plant.…”
Section: Discussionsupporting
confidence: 91%
“…According to Uprety et al (2009), application of acidified manure can considerably increase the soil micronutrient contents; and in our case manure was provided as a base material which enhanced the micronutrients bioavailability and improved the growth and yield of maize (Bakry et al, 2009;Kruczek, 2005;Lisuma et al, 2006;Singh et al, 2009). Our findings were also in line with Tariq et al (2014); Ghaffari et al (2011);Lana et al (2007) and Baloch et al (2008) who revealed that micronutrients played a critical role in achieving higher yield and growth in maize plant.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary application of zinc increased harvest index, may be due to maximum dry matter partitioning towards grain, hence the grain yield was more by the application of zinc. Similarly, Ghaffari et al, (2011) reported increase in the harvest index of maize due to application of zinc. Iron helps in utilization of nitrogen.…”
Section: Effect Of Nutrientsmentioning
confidence: 93%
“…Moreover, plant height is a response indicator, both for classification in terms of genotype difference and for the inputs applied to assess vegetal growth performance [34].…”
Section: Effect Of Nejayote On the Cultivation Of Maize Plantsmentioning
confidence: 99%